Decentralized Non-Derivative Algorithm for Real-Time Optimising Control of Large-Scale Industrial Processes - Abdullah, Normah; Tau Han, Cheong; Jailani Mohd. Nor, Mohd.; Mohamed Haris, Sallehuddin (International Journal of Engineering and Technology, 2019)
Designing controller systems for large-scale processes in a centralized form are faced with computational burden due to the large number of decision variables involved, however these difficulties can be overcome by decentralization or decomposition of the optimal control problems into smaller sub-systems in a hierarchical manner. Hence, this paper presents a decentralized adaptive real-time optimizing (RTO) control scheme for determining and maintaining the optimum steady-state operating conditions for inter-connected large scale industrial processes. The proposed strategy extends the applicability of the centralized non-derivative algorithm and by structuring it hierarchically in a decentralized fashion as in the Integrated System Optimisation and Parameter Estimation (ISOPE) technique. The proposed algorithm has been formulated in two different ways of utilising the available measurement from the plants: the first method employs input-output feedback and the second method uses only output feedback. The simulation examples are provided to illustrate and compares the methods in which the results show that the algorithm with input-output structure performs better with less number of set-point changes and faster convergence. Since the algorithm is designed in the decentralize form, the computation difficulties may adequately be dealt with.Â Â